PENGALAMAN SISWA DALAM PASARAN MINUMAN KESEHATAN TRADISIONAL : ENTERPRENUERSHIP LESSON - Nisya Kartiko Dewi; Fatimah Khumaira (HAMKA INSIGHT, 2022)
This research was conducted to find out how the utilization of business opportunities carried out by the entrepreneur even in the midst of the covid-19 pandemic. This article used qualitative research methods with a descriptive approach, observed by what’s going on around, and with the type of research used is the depiction of the phenomenon that was happening. The result of this research was this entrepreneur could saw the opportunities well, even in the pandemic period, then make a creation of entrepreneurial and marketing activities of a product that named "Jahe Super cap Jempol", with the business strategy used is social media marketing, this is related to the development of marketing digital of the industrial revolution. The covid-19 pandemic is also one of the reasons why social media marketing or digital marketung were chosen as a business strategy in marketing products. From this researched, can be concluded that the pandemic situation actually doesn’t hinder us to make or build a business, but instead it can opened opportunities for entrepreneurship. It just how we can see and take advantage from the business opportunity and make the opportunity to be money.